Exclusive History Of Asi With Stunting Events In A Childhood: Riwayat Asi Ekslusif Dengan Kejadian Stunting Pada Balita - Elma Nur Alfian; Cholifah (Universitas Muhammadiyah Sidoarjo, 2021)
Stunting is a condition in which a toddler’s growth and development does not match hias age. Meanwhile, exclusive breastfeeding without adding or replacing it with other foods or drinks given to babies from birth to 6 monts of age. The incidence prevalence data in Sidoarjo, precisely in Terik village, is (0,8%) of the 226 children under five who are stunting. This shows the hugh incidence of stunting in Terik Village, so it is necessary to carry out further studies. The purpose of this study was to determine the history of exclusive breasfeeding with the incidence of stunting in children under five.The research design used is a descriptive method and a questionnaire data collection instrument. The total population of 20 chidren under five who participated in the posyandu in Terik village was the subject of the study. Data presented in the form of frequency distribution tables and analyzed descriptively without statistical tests.The result showed that majority (55%) of children under five were not exclusively breastfed, a small proportion (10%) of children under five at the Posyandu as Terik villagewere stunted. Toddlers who are exclusively breastfed are not stunted (100%) more than those who are not exclusively breastfed (81,8%).The conclusion of this study is that children who are exclusively breastfed are not stunted more than those who are not exclusively breastfed, suggest that health workers provide health information or socialization to the public for early stunting prevention.